Evaluation of the results of simultaneous open rhinoplasty and Abbe flap for the reconstruction of the secondary bilateral cleft and nasal deformity. Issue 6 (June 2015) - Eski, Muhitdin; Aykan, Andac; Alhan, Dogan; Zor, Fatih; Isik, Selcuk
Summary: Aims: We aimed to evaluate the results of simultaneous rhinoplasty and Abbe flap for the reconstruction of the secondary bilateral cleft and nasal deformity by means of a newly developed software-based method. Patients and Methods: A total of 16 patients with the bilateral cleft lip nasal deformity received Abbe flap and simultaneous open rhinoplasty between 2004 and 2010. The mean age of the patients was 21 years, and the average follow-up time was 2.4 years. After the open rhinoplasty procedure, the upper lip was reconstructed with the Abbe flap. Preoperative and postoperative photographs that had been taken laterally were evaluated by using Adobe Photoshop ® CS4 and Adobe InDesign ® software. The length of the columella and the relative changes of the most anterior point of the upper lip to the vertical plane tangent to the most anterior point of the lower lip were measured in pixels on standardized preoperative and postoperative images. The differences were calculated and compared as a percentage (%). Results: There was no flap loss and associated problems. The measurements of columellar length revealed an average increase of 51.8 ± 11.3%, while the relative change of the most anterior point of the upper lip revealed an average increase of 68.6 ± 11.2%. Conclusion: The results of the treatment modality were successfully evaluated by a newly developed software-based method.